2005
DOI: 10.1007/s10529-005-0687-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of alginate?chitosan microcapsules: an alternative to liver cell transplants for the treatment of liver failure

Abstract: The application of alginate-chitosan (AC) microcapsules to liver cell transplantation has not been previously investigated. In the current in vitro study, we have investigated the potential of AC microcapsules for the encapsulation of liver cells and show that the AC membrane supports the survival, proliferation and protein secretion by entrapped hepatocytes. The AC membrane provides cell immuno-isolation and has the potential for cell cryopreservation. The AC microcapsule has several advantages compared to mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(49 citation statements)
references
References 22 publications
2
47
0
Order By: Relevance
“…However, the encapsulation procedure and the polymers used are not described and the capsules' mechanical properties are not assessed. Haque et al 29 have shown the viability of hepatocytes encapsulated in alginate-chitosan for 24 days.…”
Section: Discussionmentioning
confidence: 99%
“…However, the encapsulation procedure and the polymers used are not described and the capsules' mechanical properties are not assessed. Haque et al 29 have shown the viability of hepatocytes encapsulated in alginate-chitosan for 24 days.…”
Section: Discussionmentioning
confidence: 99%
“…These types of hydrogel are particularly useful in examining cellular behaviour owing to their biocompatibility, biodegradability and biofunctionality [68]. cornea agarose-fibrin [29] alginate-gelatin nanofibre [163] collagen [146,149,150] collagen-PLGLA nanofibre [160] alginate [34] cellulose [35] heparin [36] alginate-hyaluronic acid [33] collagen [190] collagen-chitosan [32] dextran [30,31] hyaluronic acid [44] alginate [27] collagen [23,24] dextran [25] gelatin [26] collagen [17,97] fibrin [37] agarose [51,175,179,196] alginate [126] chitosan [20,50] fibrin [42,51] gellan gum [22,51] hyaluronic acid [110] PEG [60] A key factor when examining cell-material mechano-interactions is the mechanisms of cell adhesion to the hydrogel. Cell surface receptors such as integrins bind to ligands within the hydrogel if such adhesion sites exist.…”
Section: Cell-mediated Remodelling Of Hydrogelsmentioning
confidence: 99%
“…As these highly confluent lymphocytes secrete a high amount of cytokines, the viability of the encapsulated cells will depend on the immune-isolation properties of the capsular membrane. 13,15 Capsules were withdrawn from this co-culture from time to time in order to check the viability of the encapsulated cells with calcein AM dye following the method mentioned above.…”
Section: Immunoprotective Behavior Of the Microcapsules Against Lymphmentioning
confidence: 99%
“…30,34 Furthermore, microencapsulated cells are protected from immune rejection because leukocytes and antibodies cannot penetrate the capsule. 7,13,14 Thus, it becomes an ideal tool for allogeneic and xenogeneic transplantation. The concept of microencapsulation may therefore eliminate the requirement for immune suppressants when used in transplantations.…”
Section: Introductionmentioning
confidence: 99%